Archaeological Research at Westerplatte in the Years 2016–2022. Nine Phases of Excavation Work - Dziewanowski, Adam; Garas, Monika; Jarzęcka-Stąporek, Joanna; Kalka, Piotr; Kuczma, Filip; Naleźny-Skurzyńska, Agnieszka; Skurzyński, Adrian (Social consequences of war, 2024)
Since 2016, the Archaeological Department of the Museum of the Second World War in Gdańsk has been conducting the first systematic archaeological research in the history of the Westerplatte peninsula. The aim of the research is to locate and document material traces related to the Polish Military Transit Depot and, above all, to find the remains of all Polish soldiers killed during the defense of the peninsula. By 2022, during the nine stages of excavations, an area of almost 6000 sq. m was thoroughly examined. Geophysical research, carried out on most of the currently available area of the former Depot, indicated the places of relics of its buildings along with traces of battles fought in September 1939. Thanks to the cooperation of Polish Army sappers visitors’ safety was ensured by removing over 3,500 explosive and dangerous items from the peninsula. Over seven years of research, over 67,000 objects were obtained – objects depicting the history of the peninsula from the mid-17th century to the present day.